The Role of Citizens in Preventing Radicalism and Terrorism in Indonesia - Hamidah, Linda Tri (Journal of Creativity Student, 2019)
Pancasila was established as the ideology of the Indonesian nation to become a guideline for the life of its citizens. Pancasila teaches to live full of tolerance, but not all citizens carry out the Pancasila values. There is an anti-Pancasila movement that can lead to the formation of a radicalism and terrorism in this country. The doctrine intends to turn this country into an Islamic State which has resulted in this nation becoming an intolerant, fanatical, and exclusive. Radicalism does not stand by itself, but behind that there is an element of profit or political and ideological binding which is like fundalism or challenges the basic structure that makes religion the principle of life. In various sources of radicalism is not caused by one factor, but can be caused by many factors such as the number of poverty rates, the rapidly developing global level, and the spread of an understanding of wahhabism originating from Saudi Arabia. Conservative wahhabism into this nation has given rise to an exclusive group that likes to slander other people who are not in their group who consider it an infidel, an enemy and may be fought. Radicalism itself is the starting point for the creation of terrorism. Terrorism is the use of cruelty which is targeted at civilians to cause fear which is usually an attempt to achieve a political goal. Terrorism is misleading, although it has a different basis for political goals but they have a common goal of being willing to harm or even kill civilians.